Diversity of cell death pathways: insight from the fly ovary. - Jenkins, V.K.; Timmons, A.K.; McCall, K. (Trends in Cell Biology, 2013)
Multiple types of cell death exist including necrosis, apoptosis, and autophagic cell death. The Drosophila ovary provides a valuable model to study the diversity of cell death modalities, and we review recent progress to elucidate these pathways. At least five distinct types of cell death occur in the ovary, and we focus on two that have been studied extensively. Cell death of mid-stage egg chambers occurs through a novel caspase-dependent pathway that involves autophagy and triggers phagocytosis by surrounding somatic epithelial cells. For every egg, 15 germline nurse cells undergo developmental programmed cell death, which occurs independently of most known cell death genes. These forms of cell death are strikingly similar to cell death observed in the germlines of other organisms.